Analysis of the Gearing Theoretic between Plastic Helical Gear and Steel Worm - Hao, Yi Shu; Yue, Bin Nan; Zhu, Xin Xing (Applied Mechanics and Materials, 2010)
The gearing transmission equation was deduced by the principle of the engagement characteristics between plastic helical gear and steel worm. This paper makes an analysis on the law which is the deformation process of tooth profile and potential contact in different kinds of load by means of Hertz contact theory. The paper also uses MSC.Nastran to simulate the stress-strain status, the deformation process and arrives at the law of gearing changing, which was verified the correctness of the analysis above.